Failure of Inducing Spermatogenesis with FSH, LH and Testosterone in Vitamin A Deficient Rat - Leardkamolkarn, Vichitra; Somana, Reon; Rojananuengnit, Sasitorn; Tosukhowong, Pichit (Journal of Basic and Applied Pharmacology, 2015)
Male Fischer rats 22 days of age were fed with vitamin A free diet until becoming vitamin A deficiency. Ten rats were left as vitamin A deficient control group (). Forty-eight rats were transferred to diet supplemented with retinoic acid (, 6 mg/kg of diet) and further divided into 4 groups to be injected daily for 14 days with saline (0.1 ml), FSH (0.1 mg) + LH (0.1 mg), FSH (0.1 mg) + testosterone proprionate (TP, 0.5 mg), and with vitamin A (50 μg). One day after the last injection, final body weight was recorded and the animals were sacrificed by decapitation. Testis, thyroid, adrenal, seminal vesicle and prostate were dissected and weighed. Testes were also prepared for histological examination. It was found that retinoic acid alone or with vitamin A treated could similary induce body growth in vitamin A deficient rats. Retinoic acid with or without injections of FSH + LH or FSH + TP could equally and slightly improves the cytologic condition of the seminiferous tubules over the vitamin A deficient level. However, vitamin A injections for 14 days could further improve the condition of the seminiferous tubules. It is concluded that short-term or long-term treatments with hormone necessary for spermatogenesis without supplementation of vitamin A could not cause full spermatogenesis in rats with testicular damage due to vitamin A deficiency. However, with or without supplementation of such hormones, vitamin A could induce full spermatogenesis.